Alloy engineering of two-dimensional transition metal dichalcogenides - Liu, Sheng (2019)
The two-dimensional (2D) transition metal dicalcogenides (TMDs) have taken over the tremendous research attention from graphene in the last decade. The MX2 (M=Mo and W; X=S, Se and Te) honeycomb lattice down to monolayer limit has direct band gap and large excitonic effect due to the out-of-plane quantum confinement. The robust excitonic levels with binding energy up to ∼200 meV make TMDs become increasingly important for a variety of applications including photo-detectors, high-power transistors and other optoelectronics. The translation momentum, spin angular momentum and orbital angular momentum together in this 2D system are linked by spin-valley coupling, which gives rise to valleytronics and valley-related physics. To fulfill the potential of valleytronics applications, stable valley polarization via intravalley recombination of the excitons need to be revealed. Prominent valley polarization in TMDs exists only at liquid nitrogen temperature regime. For years researchers have been trying to solve the depolarization mechanism and to make the valley polarization last to higher temperatures, or even room temperature. However, there is still no convincing conclusions. Previous works report various valley behaviors case-by-case. For example, most high temperature valley effects are observed in WX2, while MoSe2 seems to have no valley response even down to liquid helium temperature. Here in this thesis, by making ternary alloy MoS2(1−x)Se2x, the intra- and intervalley dynamics of the excitons can be studied systematically, in the same lattice system with modulated energy band structure. From studying this exciton dynamics, we hope to uncover the mechanism of intervalley depolarization and the strategy to enhance the valley effects. Firstly, we studied the band gap and spin-orbit engineering among the alloyed monolayers based on temperature dependent reflectance and photoluminescence spectroscopy. By fitting the exciton peak with temperature, all the parameters related to the excitons including line width, energy position and phonon coupling with the lattice can be obtained for all the alloys. The Raman spectroscopy of the alloys were also studied to obtain information about their lattice symmetry and phonon energies. Secondly, the exciton fine-structures with one bright and one dark states were probed by monitoring the temperature-dependence of the exciton PL intensity, combining with the time-resolved photoluminescence spectroscopy which can qualitatively measure the radiative lifetimes. Lastly, the inter-valley depolarization has been evaluated based on the modulated bright-dark split energy ∆BD among the alloys. At last, we also explored the heteroatomic doping of MoSe2 crystal with magnetic dopant manganese. High quality Mo-doped single crystal is grown by chemical vapor transport reaction (CVT) method, and monolayer to fewlayer samples can be exfoliated. We then carefully studied the optical and electronic properties, interlayer and intralayer phonon modes of the samples by PL and Raman spectroscopy. The first-principles calculation were used to calculate the localized magnetic ordering of the Mn-doped crystal.